Beyond the Definition of Metabolic Syndrome: Uric Acid, High Sensitivity C Reactive Protein and Global Cardiovascular Risk - Jorge Vega Abascal; Mayra Rosa Guimara Mosqueda; Luis Vega Abascal (Correo Científico Médico, 2017)
Introduction: the metabolic syndrome is becoming one of the main problems in public health.